Water‐Harvesting Metal–Organic Frameworks with Gigantic Al24 Units and their Deconstruction into Molecular Clusters. (29th December 2022) - Xu, Huoshu; Wu, Yichen; Yang, Lingyi; Rao, Yin; Wang, Junyi; Peng, Shuyin; Li, Qiaowei
Abstract: In contrast to the vast Al‐oxo molecular cluster chemistry, Al‐based building units for metal–organic framework (MOF) construction are limited in structural diversity and complexity. Synthesis of single crystalline MOFs based on this "hard" metal is further complicated by the poor reversibility of the Al‐organic coordination linkages. Here, a strategy to employ two kinds of linkages with distinct strength—strong Al‐carboxylate linkage and weak Cu‐pyrazol N linkage—gives FDM‐91 (FDM=Fudan Materials) with gigantic Al24 ‐based units. After replacing the weak moieties with organic linkers post‐synthetically, two new stable MOFs with exceptional water harvesting capacity (up to 0.53 g g −1 ) and outstanding cycling performance are developed. Linkage‐selective dissociation of FDM‐91 further leads to the isolation of the Al24 molecular clusters. The versatile chemistry performed here to reinforce or deconstruct MOFs provides a new way to make important extended and discrete structures. Abstract : A dual‐linkage strategy to make single crystalline metal–organic frameworks (MOFs) gives porous solids with gigantic Al24 units. Selective linkage replacement rigidifies the MOFs resulting in outstanding water‐harvesting behaviour. The selective linkage dissociation of the MOF provides a new route to prepare highly symmetrical clusters.